Social Studies for Civic Education Practice in Japan: a Case Study of Human Rights Learning through Participatory Approach in Junior High School 3rd Grade - Shirai, Katsuhisa (The Indonesian Journal of Social Studies, 2020)
This research aims to emphasize the characteristics of social studies for civic education practice in Japan through a case study of junior high school 3rd grade practice of â€œhuman rights learning through participatory hands-on learningâ€ and to show comparative viewpoints on social studies in Indonesia. The following points became clear as a result of this research. First, through the unit of social studies and civic education, students could have fun and realize the value of human rights by adopting a participatory experiential approach to learning with the inclusion of workshops and simulated trials. This point is one of the important characteristics of citizenship in a democratic society. Second, in a social studies and civic education class, the students actively respected othersâ€™ opinions and learned from each other by actively participating in group activities and discussions. This point forms the basis of the citizenship necessary to form a democratic society. The above two points are thought to have implications for the social studies for civic education in Indonesia.